Measuring the Hydraulic Conductivity of Grass Root Systems. Issue 2 (20th April 2020) - Gal, Atara; Hendel, Elisha; Peleg, Zvi; Schwartz, Nimrod; Sade, Nir
Abstract: Root‐system hydraulic conductivity (RSHC) is an important physiological characteristic that describes the inherent ability of roots to conduct water across a water‐potential gradient between the root and the stem xylem. RSHC is commonly used as an indicator of plant functioning and adaptability to a given environment. A simple, fast, and easy‐to‐use protocol is described for the quantification of RSHC at the seedling stage in two important monocot species grown in hydroponic solution: Setaria viridis, a C4 model plant, and wheat, a C3 crop plant. This protocol can also be easily modified for use with almost any grass species and environmental treatments, such as salinity or hormone treatments. © 2020 by John Wiley & Sons, Inc. Basic Protocol : Setaria hydrostatic root‐system hydraulic conductivity Alternate Protocol : Measuring the root conductivity of young plants with soft stems